Status of Elementary-School Counselling in Six Canadian Provinces - Oksanen, Ilkka; Van Hoose, William (Canadian Journal of Counselling and Psychotherapy, 2012)
This study was an attempt to investigate several aspects of elementary-school counselling in Canada. The number of counsellors employed, their professional background, certification, and provincial standards for guidance were examined. In the six responding provinces whose data were usable, a total of 267 counsellors were employed in the elementary schools with approximately half of that number employed on a full-time basis. About 18 percent held a graduate degree in guidance; 75 percent had an undergraduate degree with guidance qualifications; while 7 percent had no degree but some guidance training. Only 2 of the 6 provinces providing data had certification requirements for elementary-school counsellors and only 2 had developed standards for counsellors in the elementary schools.